Insects in agricultural greenhouses: a metagenomic analysis of microbes in Trialeurodes vaporariorum infesting tomato and cucumber crops - Qush, Abeer; Assaad, Nada; Alkhayat, Fatima Abdulla; Al-Kuwari, Mohammed Saif; Al-Khalaf, Nasser; Bassil, Maya; Yassine, Hadi M.; Zeidan, Asad; Razali, Rozaimi; Kamareddine, Layla (Frontiers in Plant Science, 2025)
IntroductionWith the predicted 9-10 billion world population increase by 2050 and its accompanying need for sustainable food production, and with the harsh climate conditions challenging agriculture and food security in many countries world-wide, employing “horticultural protected cultivation practices” in farming for seasonal and off-seasonal crop production is on the rise, among which is the use of agricultural greenhouses. The importance of greenhouse farming has been, indeed, evident by the perceived increase in year-round crops production, curtail in production risks, upsurge in agricultural profits, outreaching food stability and security in many countries globally. Yet, and despite this acknowledged success of employing greenhouses in farming, many constraints, including the presence of insect pests, still chaperoned this practice over the years, significantly impacting crop quality and production.MethodsAs such, we assessed in this study the status of “insect pests” in the greenhouse model by collecting insects from different greenhouse sectors grown with tomatoes and cucumbers and identified the collected insects using relevant identification keys. To further explore the pest paradigm in greenhouses, we then focused on particularly studying Trialeurodes vaporariorum (TRIAVA), a key insect species among the collected and identified insects in the studied greenhouse model and a significant pest with an impactful effect on many crops worldwide. To do so, we traced the abundance of TRIAVA in the tomato and cucumber grown greenhouse sectors over the period of the study, analyzed its metagenome and associated its abundance with crop yield.Results and discussionOur findings revealed TRIAVA hosted microbes with aptitudes to either serve as symbiotic microorganisms and protect TRIAVA against pathogens or to potentially cause damage to crops. This work provides additional insight into the insect pests paradigm in greenhouses, an upshot that could serve integrated insect pest management strategies in greenhouses for optimal agricultural practices.